Landscape architecture in the Ag-Ed classroom: cultivating the next generation of designers - Wilson, Erin Marie (Kansas State University, 2016)
Landscape architecture education in schools have been focused primarily on elementary and secondary Common Core courses. In many states, career-oriented programs such as agricultural education serve as a platform to teach necessary skills to be successful in all aspects of the agricultural industry. With the shift in lifestyles and technology, agricultural education (Ag-Ed) today has branched out from the traditional farm management courses to food science, natural resources, and landscaping design as well as many others. At schools like Lennox High School in Lennox, South Dakota, students learn plant identification, fundamentals of landscape design, and design graphics. How comprehensive are students' awareness of the landscape architecture profession before, during, and after taking a landscaping course? What are the possibilities of reinforcing foundational skills learned in the landscaping coursework through an outdoor learning environment similar to practical application of other vocational-type courses? How could students be presented a snapshot of the landscape architecture profession that connects the current and future curriculum taught in the Ag-Ed classroom? In order to better understand the landscape architectural aspects of current Ag-Ed, a mixed methods approach was used. First, national, state, and local Ag-Ed curricula standards were reviewed to track how Ag-Ed courses and priorities have changed over time. Next, Ag-Ed students were surveyed before, during, and after taking the Landscaping and Horticultural course offered at Lennox High School to assess potential changes in awareness. Lastly, students currently taking the landscaping course participated in a three-day workshop where they developed ideas for their outdoor learning environment to support current and future Ag-Ed courses and landscape architecture. After the workshop, these students took a post-survey to evaluate ideas produced in the workshop, the future implementation of the workshop, and their level of awareness of the landscape architecture profession. Results from the surveys and workshop show a refinement and increase in landscape architecture awareness, a desire for more hands-on learning conducted outside, and an enthusiasm for using their creativity to design a project for future Ag-Ed students. In subsequent years, future iterations of the workshop will advance planning and design proposals toward implementation.
Keywords: Landscape architecture; Ag-Ed; Agricultural education; Landscaping; FFA; Agriculture